Revitalizing Traditional Colenak Cuisine Through Digital Platform Engagement Among Younger Generations - Aditiya Faturahman; Salwa Anisa; Rasya Putri Falisha; Putra Salman Alfarizi Santoso; Nesa Nesa; Muhammad Akmal; Diana Syahira; Delia Fazriah; Adi Bil Haq; Itto Turyandi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the revitalization of colenak as a traditional culinary heritage through the utilization of digital platforms among younger generations. The research addresses the declining interest in traditional food caused by changing consumption patterns shaped by visual culture, digital trends, and contemporary lifestyle preferences. An empirical qualitative approach grounded in interpretive analysis was employed through in depth interviews with colenak business actors, literature review, and digital platform observation. The findings reveal that the decreasing relevance of colenak is associated with limited visual innovation, weak digital promotion, and the transformation of youth consumption behavior emphasizing symbolic and aesthetic experiences. Digital platforms were identified as effective instruments for strengthening consumer engagement through cultural storytelling, interactive communication, and visual branding strategies. Product adaptation through flavor innovation and creative presentation also contributed to improving market acceptance while maintaining culinary authenticity. The study further demonstrates that cultural sustainability depends upon intergenerational participation, educational involvement, and community based preservation efforts. The integration of cultural authenticity, entrepreneurial adaptation, and digital engagement provides an important framework for sustaining traditional culinary heritage within contemporary digital society.